DIGITAL IMAGE ENCRYPTION USING RSA AND LFSR - Gandhi, Srushti; Gor, Ravi (International Journal of Engineering Science Technologies, 2022)
In this world of hasty evolution of exchanging digital data, data protection is essential to keep the data safe from the unauthorized parities. With the broad use of digital images of various fields, it is important to preserve the confidentiality for the data of an image from any unauthorized access. In this paper, the keys are generated using a random number generator which is based on Linear Feedback Shift Register (LFSR). The encryption/decryption is based on Rivest–Shamir–Adleman (RSA) with the random key generator.